The G⁵¹⁶T CYP2B6 germline polymorphism affects the risk of acute myeloid leukemia and is associated with specific chromosomal abnormalities. - Aggeliki Daraki; Sophia Zachaki; Theodora Koromila; Paraskevi Diamantopoulou; Gabriel E Pantelias; Constantina Sambani; Vasiliki Aleporou; Panagoula Kollia; Kalliopi N Manola (PLoS ONE)
The etiology of acute myeloid leukemia (AML) underlies the influence of genetic variants in candidate genes. The CYP2B6 enzyme detoxifies many genotoxic xenobiotics, protecting cells from oxidative damage. The CYP2B6 gene is subjected to a single-nucleotide polymorphism (G⁵¹⁶T) with heterozygotes (GT) and homozygotes (TT) presenting decreased enzymatic activity. This case-control study aimed to investigate the association of CYP2B6 G⁵¹⁶T polymorphism with the susceptibility of AML and its cytogenetic and clinical characteristics. Genotyping was performed on 619 AML patients and 430 healthy individuals using RCR-RFLP and a novel LightSNip assay. The major finding was a statistically higher frequency of the variant genotypes (GT and TT) in patients compared to the controls (GT:38.8% vs 29.8% and TT:9.3% vs 5.3% respectively) (p<0.001). More specifically, a significantly higher frequency of GT+TT genotypes in de novo AML patients (46.6%) and an immensely high frequency of TT in secondary AML (s-AML) (20.5%) were observed. The statistical analysis showed that the variant T allele was approximately 1.5-fold and 2.4-fold higher in de novo and s-AML respectively than controls. Concerning FAB subtypes, the T allele presented an almost 2-fold increased in AML-M2. Interestingly, a higher incidence of the TT genotype was observed in patients with abnormal karyotypes. In particular, positive correlations of the mutant allele were found in patients carrying specific chromosomal aberrations [-7/del(7q), -5/del(5q), +8, +21 or t(8;21)], complex or monosomal karyotypes. Finally, a strikingly higher frequency of TT genotype was also observed in patients stratified to the poor risk group. In conclusion, our results provide evidence for the involvement of the CYP2B6 polymorphism in AML susceptibility and suggest a possible role of the CYP2B6 genetic background on the development of specific chromosomal aberrations.